Variable Pay and Risk Sharing Between Firms and Workers - Jason Sockin; Michael Sockin (Institute of Labor Economics (IZA), 2025)
Firms differ in the extent to which they use variable pay. Using U.S. employeeemployer matched data on variable pay from Glassdoor, we document such dispersion and find workers are exposed to firm-level shocks through variable pay. Credit rating downgrades from investment to speculative grade, negative shocks to financial or operational performance, and greater exposure to a financial crisis, as proxied for by the collapse of Lehman Brothers, induce firms to shift compensation toward base pay. Increased use of variable pay is associated with greater earnings variance for workers but less volatile growth for firms. We rationalize these findings in a model of risk sharing between a risk-averse firm and workers with limited commitment.
Keywords: J33; E24; 330; risk sharing; bonuses; firm-specific shocks; employment volatility; layoffs